2005
DOI: 10.1128/mcb.25.6.2200-2215.2005
|View full text |Cite
|
Sign up to set email alerts
|

BAF57 Governs Androgen Receptor Action and Androgen-Dependent Proliferation through SWI/SNF

Abstract: Androgen receptor (AR) activity is required for prostate cancer development and progression. Thus, there is a major impetus to understand the regulation of AR action. We and others have previously shown that AR transactivation potential is dependent on the presence of an active SWI/SNF chromatin remodeling complex. However, the mechanisms underlying SWI/SNF regulation of the AR remained unsolved. We show here that the BAF57 subunit, an accessory component of the remodeling complex, is a critical regulator of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 79 publications
4
103
1
1
Order By: Relevance
“…BAF57 binds to and is required for both estrogen and androgen receptor function (Belandia et al, 2002;Link et al, 2005). Preliminary data suggest that BAF57 may also regulate estrogen receptor expression (unpublished data), but the expression of BAF57 in primary tumors has not yet been investigated and the role of BAF57 in the etiology of ER-negative breast cancer remains to be determined.…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…BAF57 binds to and is required for both estrogen and androgen receptor function (Belandia et al, 2002;Link et al, 2005). Preliminary data suggest that BAF57 may also regulate estrogen receptor expression (unpublished data), but the expression of BAF57 in primary tumors has not yet been investigated and the role of BAF57 in the etiology of ER-negative breast cancer remains to be determined.…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…Although it has not been investigated, the loss of BRG1 and BRM could very well underlie the resistance to glucocorticoids in hematopoietic malignancies such as myeloma, lymphoma and leukemia, as well as in lung cancer (Choi et al, 2001b;Ko et al, 2004;Pottier et al, 2007). The estrogen receptor is also functionally linked to the SWI/SNF complex Belandia et al, 2002), and the androgen receptor is also SWI/SNF dependent (Inoue et al, 2002;Marshall et al, 2003;Hong et al, 2005;Link et al, 2005;Dai et al, 2008). We have found that BRG1 and BRM are lost in human prostate cancer samples, suggesting that a loss of SWI/SNF function may play a role in the development of hormone-refractory prostate cancer.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…Chromatin immunoprecipitation experiments have demonstrated the presence of hSWI/SNF components on the promoters of IFNgand IFNa-inducible genes, as well as on the IFNb promoter (Agalioti et al, 2000;Huang et al, 2002;Liu et al, 2002;Pattenden et al, 2002;Cui et al, 2004). hSWI/SNF is also present on the CD44 and E-cadherin promoters (Banine et al, 2005;Gresh et al, 2005), on the promoters for myogenin and muscle creatine kinase (Simone et al, 2004), and on steroid receptor targets (Fryer and Archer, 1998;DiRenzo et al, 2000;Belandia et al, 2002;Me´tivier et al, 2003;Link et al, 2005). Despite the growing knowledge of promoters regulated by hSWI/SNF, it is not well understood how the complex becomes localized and activated at various promoters; however, there is evidence for the involvement of signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatin remodeling ability of hSWI/SNF has been shown to respond to various signaling pathways, including response to phosphoinositols (Zhao et al, 1998;Rando et al, 2002), the p38 pathway during skeletal myogenesis (Simone et al, 2004), interferons (Agalioti et al, 2000;Huang et al, 2002;Liu et al, 2002;Cui et al, 2004) and nuclear hormone receptors (Fryer and Archer, 1998;DiRenzo et al, 2000;Belandia et al, 2002;Me´tivier et al, 2003;Link et al, 2005). Phosphatidyl inositol 4,5-bisphosphate (PIP 2 ) has been shown to help increase the association of the SWI/SNF complex with the nuclear matrix (Zhao et al, 1998;Rando et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node prostate cancer cells were transfected, treated with 10 nM DHT for 3 h and harvested for ChIP analysis as previously described (Link et al, 2005), with modifications described in Supplementary Information.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%